1980
DOI: 10.1046/j.1537-2995.1980.20180125038.x
|View full text |Cite
|
Sign up to set email alerts
|

Complement changes during leukapheresis

Abstract: Alterations of the complement system occurring during continuous‐flow filtration leukapheresis (CFFL) and intermittent‐flow centrifugation leukapheresis (IFCL) were assessed in 16 donors. Five blood samples were obtained at timed intervals during each cytaphere‐sis, three directly from each donor and two from the efferent lines returning blood from the leukapheresis machines to the donors. Components measured were C1, C2, C4, C3, C3‐C9 and CH50 of the classical, and factor B, properdin and properdin convertase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…This saturation and/or deactivation may then result in diminished chemiluminescence upon stimulation. In contrast to filtration cytapheresis, complement activation is unlikely to occur during centrifugation cytapheresis (11). Complement acitvation is characteristically accompanied by increased chemiluminescence activity by stimulated cells (5,10) and clinical symptoms of pulmonary sequestration of leukocytes (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This saturation and/or deactivation may then result in diminished chemiluminescence upon stimulation. In contrast to filtration cytapheresis, complement activation is unlikely to occur during centrifugation cytapheresis (11). Complement acitvation is characteristically accompanied by increased chemiluminescence activity by stimulated cells (5,10) and clinical symptoms of pulmonary sequestration of leukocytes (9).…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of complement activation (11) and functional analysis of monocytes and lymphocytes during cytapheresis have been reported (12,13). Similar studies with granulocytes, however, remain to be performed.…”
mentioning
confidence: 92%
“…These results based on humoral parameters do not indicate a filtration-mediated impairment of the integrity of granulocytes, whereas erythrocytes were slightly fragile after 5 days of storage. It has been shown that plasma, after travelling through various extracorporeal circuits, äs commonly occurs in techniques such äs filtration cytapheresis (26), haemodialysis (7) and cardiopulmonary bypass (12), generates distinct granulocyte-activating products. These complement-splitting products (C5a) and immune complexes are potent Stimuli, causing increases in aggregation and respiratory burst activity (chemiluminescence) of granulocyte target cells.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies by Nusbacheret al [43] and Strauss et al [44] showed that in addition to complement activation, absorption to the fil ter of some complement proteins, mainly properdin, occurs during LP and plays a role in reducing serum hemolytic titers.…”
Section: Leukapheresismentioning
confidence: 99%